Time Management for Department Chairs - Hansen, Christian K. (Jossey - Bass, 2011)
This book is not about creating more time but rather about making the best use of the time we have. Much of what is disscussed in this book is about creating balance: Balancing chair and faculty workload, balancing time spent on the various duties of the chair position, balancing work and family, and so on.